A Dual-Process Approach to Understanding Human-Robot Interaction. (September 2013) - Lobato, Emilio J. C.; Wiltshire, Travis J.; Fiore, Stephen M.
Human-robot interaction (HRI) research needs to leverage the theories and findings from multiple disciplines to inform subsequent empirical investigation and robot design. Utilizing evidence and suggestions from social cognitive and neurocognitive disciplines for human-human interaction, we propose an approach for conceptualizing HRI. Comparing HRI to human-human interaction at the surface level and deeper levels allows for the generation and evaluation of testable hypotheses in multiple disciplines to inform the design of future robotic systems.